Comparative Study of Conventional Impressions vs Intraoral Scanning for Complete Denture Fabrication - Priya Nagar; D Anupama Prasad; Sukanta K. Satapathy; T. Vigneswaran; Mariea Francis; Avantika Vijaysingh Jadhav (Journal of Pharmacy and Bioallied Sciences)
Background: Conventional impression techniques for complete denture fabrication, although traditional, often pose challenges regarding accuracy and patient comfort. Intraoral scanning offers a digital alternative that promises enhanced precision and patient satisfaction. This study aimed to compare the efficacy, accuracy, and patient outcomes between conventional impression methods and intraoral scanning for the fabrication of complete dentures. Materials and Methods: A total of 100 edentulous patients were randomly assigned to two groups: one group receiving conventional impressions (n = 50) and the other undergoing intraoral scanning (n = 50). The primary outcome measures included impression accuracy (assessed by comparing final denture fit), time efficiency (total clinical time from impression to denture delivery), and patient satisfaction (evaluated through a standardized questionnaire). Statistical analysis was performed using the Chi-squared test for categorical data and t-tests for continuous variables. Results: The intraoral scanning group demonstrated significantly higher accuracy in denture fit, with 92% of patients reporting excellent fit compared to 74% in the conventional group (P < 0.05). Time efficiency was also enhanced in the intraoral group, with a reduction in total clinical time of 25%. Patient satisfaction scores were notably higher in the intraoral scanning group (8.6 ± 0.5 on a 10-point scale) compared to the conventional group (6.9 ± 1.0). No significant complications were reported in either group. Conclusion: Intraoral scanning proves to be a superior technique for the fabrication of complete dentures compared to conventional methods, offering better denture fit, reduced clinical time, and improved patient satisfaction. These findings suggest that intraoral scanning could replace traditional impression methods in clinical practice for edentulous patients.